Coastal Engineering - Coastal Engineering (Elsevier, 2026)
Coastal Engineering is an international medium for coastal engineers and scientists. Combining practical applications with modern technological and scientific approaches, such as mathematical and numerical modelling, laboratory and field observations and experiments, it publishes fundamental studies as well as case studies on the following aspects of coastal.
FI 1.13
Q1
Keywords: Physical Sciences & Engineering; Materials Science; Ingeniería costera; Acuerdos transformativos; Transformative agreements; Estructuras portuarias; Sedimentos; Impacto morfológico; Impacto ambiental